The knowledgeable patient : communication and participation in health - Hill, Sophie; Wiley InterScience (Online service) (Oxford ; Hoboken, NJ : Wiley-Blackwell, 2011)
This book sits at the forefront of the challenging, changing 21st century health landscape. The 'knowledgeable patient' as an individual can take many forms: patient, family carer, consumer advocate or member of the public interested in health issues. In each of these roles, knowledgeable patients interact with health professionals by asking questions about the evidence for treatment, seeking support, exchanging views and contributing experience and new ideas on how to improve the health system. Drawing from several research paradigms, The Knowledgeable Patient is an essential guide to a new era of complex healthcare. Integrating consumer stories and evidence from systematic reviews, it examines key communication and participation issues in a range of contexts. It is international in scope with researched examples spanning the community, health services, governance and policy making. Its purpose is to provide health professionals and consumers with new ideas, concepts, evidence and practical tools to understand the central role of communication and participation to a well-functioning health system. It is an ideal reference for students studying the health sciences.
Does Communication with Consumers and Carers need to Improve? / Megan Prictor, Sophie Hill -- A New Conceptual Framework for Advancing Evidence-Informed Communication and Participation / Sophie Hill, Mary Draper -- Interventions for Communication and Participation: Their Purpose and Practice / Sophie Hill, Dianne B Lowe, Rebecca E Ryan -- Identifying Outcomes of Importance to Communication and Participation / Sophie Hill, Dianne B Lowe, Joanne E McKenzie -- Communicating Risk and Risk Statistics for Preventing Chronic Disease / Sophie Hill, Adrian G K Edwards, Dianne B Lowe -- What does Participation Mean? Reshaping our Understanding of the Meaning of Surgery / Sophie Hill, Jessica Kaufman -- Disclosure: A Case Study of Communication about Medically Acquired Risk for a Rare Disease / Rebecca E Ryan, Jessica Kaufman, Sophie Hill -- How I used a Systematic Review from / Helen Dilkes, Jessica Kaufman, Sophie Hill -- Evidence and Resources for Systems Decision-Making: Improving the Experience of Health and Treatment / Dianne B Lowe, Sophie Hill, Rebecca E Ryan -- Looking at Online Health Information more Critically / John Kis-Rigo -- Learning to Communicate / Megan Prictor, Simon Lewin, Brian McKinstry, Jessica Kaufman -- Getting the Most out of Research: Using what we know / Dell Horey, Jessica Kaufman, Sophie Hill -- Research Agendas for Knowledgeable Patients / Ruth Stewart, Sandy Oliver -- Managing Multiple Health Problems: Is there Evidence to Support Consumer-Focused Communication and Participation? / Rebecca E Ryan, Sophie Hill -- Partners in Care: An Evidence-Informed Approach to Improving Communication with Women in a Hospital Setting / Sophie Hill, Maureen Johnson, Mary Draper -- Building Health-Literate Societies / Sophie Hill, Dianne B Lowe, Chaojie Liu, Nancy Santesso -- Tools for Building Research Capacity and Knowledge Transfer / Helen Dilkes, Jessica Kaufman, Sophie Hill -- Emerging Technologies for Health Communication / Yannis Pappas, Josip Car.
Includes bibliographical references and index.
Print version record.
Keywords: Patient education; Health education; Health education; Patient education; Electronic resource